The Digital Constellation - Sebastian Berg; Niklas Rakowski; Thorsten Thiel (Weizenbaum Institute for the Networked Society - The German Internet Institute, 2020)
The emergence of the digital society has become one of the most pressing research topics in social science. So far, political science has been at the margins of the debate because it has been restricted by a rather narrow focus on networked communications. The paper attempts to change this by presenting a more encompassing way to address digitalisation from within political science. After briefly criticising the development of the research in political science the paper reconstructs at length some of the most popular conceptualisations in neighbouring disciplines. While we highlight the commonalities and strengths of those approaches in theorising digitalisation, we criticise their rather derivative understanding of democratic practices and the political as such. We go on to propose a modified understanding - which we term the "digital constellation" - that looks at the changing shape of democracy by developing a much more nuanced understanding of the interplay between societies and technologies. Finally, we illustrate the argument in an exemplary analysis of the changes occurring in political representation in the context of digitalisation.
Keywords: 300; Repräsentation; Demokratie; Digitalisierung; politische Theorie; Politikwissenschaft; Forschungsgegenstand